Desenvolvimento de um sistema de geração de resistência para aparelhos de musculação e fisioterapia - Siquieroli, Warner Artur (2007)
This work presents the design of an alternative resistance generation system in opposite to contraction of skeletal muscle to be applied to workout and physical therapy machines. The modeling of the proposed device uses a spring-follower-came group to produce the resistance, without weights, cables, belts or chains. The device is capable to adjust the resistant torque dynamically, keeping it proportional to a predetermined pattern, in a variable speed movement. This way, as in other devices of variable dynamic resistance (VDR), it provides the capacity of allowing ballistic movements and the motor muscles pre-stretching, however, without the speed and acceleration limitations of those machines movement. The device can control the undesirable effects of inertia in eccentric/concentric and concentric/eccentric exercises. The resistant torque can be maintained proportional to the desired profile, no matter the acceleration and angular speed prescribed, being just necessary o came profile for each situation. This device can increase both safety and accuracy to select the initial load, infinitesimal increments of resistance, low energy dissipation and a better behavior of the applied resistance for a desired movement profile. The production cost of the proposed mechanism is similar to current weight stack machines. It was designed and manufactured a device to obtain the biceps torque curves. It will be showed in this work the system mathematical modeling and its numeric solution by using mechanical simulation software.